Promoting Picture Word Inductive Model (PWIM) to Develop Students’ Writing Skill - Fitri Novia (Premise: Journal of English Education and Applied Linguistics, 2015)
Abstract: The objective of this study was to find out whether or not there was significant difference between students who were taught using picture word inductive model (PWIM) and that of those who were not. The experimental method was used to conduct the study. The population of this study was the eighth grade students in SMP N 1 Sirah Pulau Padang.  Out of this pouplation, 68 students were taken as a sample and were divided  equally into two groups by using purposive sampling method. Therefore, class VIII 1 was the experimental group whereas VIII 3 as the control group, each of them consists of 34 students. The data were collected by asking students to write descriptive paragraph. To find out the validity, content validity was used. Inter-rater reliability was used to find out the reliability. T-test was used to analyze the data. Based on the result, the value of t-obtained was 3.155, at the significant level p<0.05 in two tailed testing with do = 66, the critical value of t-table = 1.9966. Since the value of t-obtained was higher than t-table, the Null Hypotheses (Ho) was rejected and Alternative Analysis (Ha) was accepted. It meant that there was significant difference between students who were taught using picture word inductive model (PWIM) and that of those who were not. In conclusion, PWIM could help students to develop writing skill. Key Word: Writing skill, Picture Word Inductive Model (PWIM).